The Influence of Human Resource Quality, Work Professionalism, and Work Commitment on Employee Performance - Badrianto, Yuan; Sapruwan, Muhammad (International Journal of Applied Finance and Business Studies, 2024)
This study investigates the influence of Human Resource Quality, Work Professionalism, and Work Commitment on Employee Performance in the context of Indonesian manufacturing companies. Amid increasing competition and a demand for productivity, optimizing employee performance has become a strategic imperative. Employing a quantitative causal research design, the study collected data from 62 manufacturing employees through structured questionnaires and analyzed the data using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that Organizational Commitment has a significant and positive effect on Employee Performance, while Human Resource Quality shows a positive but statistically insignificant influence. In contrast, Work Professionalism demonstrates a negative and non-significant relationship with performance. These results suggest that enhancing employee commitment plays a pivotal role in driving performance, whereas the effects of human resource quality and professionalism may depend on additional organizational factors. The study offers practical insights for human resource development strategies and contributes to the literature by simultaneously analyzing these three constructs in a manufacturing setting.